(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Medical waste management is an important component of the healthcare system aimed at ensuring the sanitary and epidemiological safety of the population and protecting the environment. Medical waste includes a wide range of materials, from used dressings and syringes to remnants of medicines and biological samples. Their improper handling can lead to the spread of infections, chemical contamination and injury. The abstract discusses the main categories of medical waste, the regulatory framework, and the stages of its collection, storage, transportation, neutralization, and disposal. Special attention is paid to modern recycling methods, the role of personnel and training requirements in the field of safe waste management. An effective medical waste management system is the key to the safe and sustainable operation of medical institutions.